Quantification of quantum dot murine skin penetration with UVR barrier impairment. Issue 8 (December 2012) - Mortensen, Luke J.; Jatana, Samreen; Gelein, Robert; De Benedetto, Anna; De Mesy Bentley, Karen L.; Beck, Lisa A.; Elder, Alison; DeLouise, Lisa A.
Abstract Ultraviolet radiation (UVR) skin exposure is a common exogenous insult that can alter skin barrier and immune functions. With the growing presence of nanoparticles (NPs) in consumer goods and technological applications the potential for NPs to contact UVR-exposed skin is increasing. Therefore it is important to understand the effect of UVR on NP skin penetration and the potential for systemic translocation. Previous studies qualitatively showed that UVR skin exposure can increase the penetration of NPs below the stratum corneum. In this work, an in vivo mouse model was used to quantitatively examine the skin penetration of carboxylated (CdSe/ZnS, core/shell) quantum dots (QDs) through intact and UVR barrier-disrupted murine skin by organ Cd mass analysis. Transepidermal water loss was used to measure the magnitude of the skin barrier defect as a function of UVR dose and time post-UVR exposure. QDs were applied to mice 3–4 days post-UVR exposure at the peak of the skin barrier disruption. Our results reveal unexpected trends that suggest these negative-charged QDs can penetrate barrier intact skin and that penetration and systemic transport depends on the QD application time post-UVR exposure. The effect of UVR on skin-resident dendritic cells and their role in the systemic translocation of these QDs are described. Our results suggest that NP skin penetration and translocation may depend on the specific barrier insult and the inflammatory status of the skin.